THE TOURIST MOTIVATION OF LINGGAM CAHAYA’S MUSEUM IN LINGGA DISTRICT ON RIAU ISLAND - Sri Juniarti; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Respon in the world of tourism is the opinion of way of view of visitors and tourists in understanding a tourist destination. This research was conducted inlinggam cahaya’ Museum on Muhammad Yusuf, Daikstreet, lingga district kepulauan riau- indonesia. this study aims to determine the response tourists motivation of linggam cahaya museum. this research uses quantitative descriptive method to process the data obtained in the field through interviews, observations and questionnaires. all the information collected and studied to become a unified whole (Sugiyono 2000). As for the sample in research 100 respondent. The determinantion of respondents with accidental sampling.Data collection techniques used are observations, interviews, questionnaires, using Likert scale as a measuring tool. Based on the results of research that has been donethe implementation of respontourists motivation of linggam cahaya museumwith sub variablethe main Attraction, Motivation and responsibilities with good category conclusions. Keywords :Motivation, Respon of Tourists,and Museum